Pengembangan Game Edukasi Tentang Mata Menggunakan Metode Research And Development Untuk Kelas IIX - Andriyanto, Sidhiq; Afriansyah, Riki; Syafiq, Ikmal (Manutech : Jurnal Teknologi Manufaktur, 2024)
Information technology-based learning has become a primary focus in improving the effectiveness of the educational process in various institutions. The background of this research is driven by the need of SMP Negeri 2 Parittiga to utilize information technology as an innovative and engaging learning tool for Grade IX students. This is due to the declining interest of students in learning science subjects at SMP Negeri 2 Parittiga. This research aims to develop an educational game application using the Research and Development (R&D) method with the Game Development Life Cycle (GDLC) as the development method. The GDLC method was chosen to ensure that the development of the educational game application is conducted in a structured and efficient manner. The design of user activities in the application uses activity diagrams, while the interface design utilizes Canva software. The development of this game application uses Unity 2D software. The result of this research is an educational game application that includes a sliding puzzle menu, materials, and practice questions for Grade IX students at SMP Negeri 2 Parittiga. The validation test using Aiken's method for content validation scored 0.9286, while media validation scored 0.8518. With these very high criteria, it can be concluded that the application is highly suitable for use by Grade IX students as a learning tool. It is hoped that this research can enhance the quality of learning at SMP Negeri 2 Parittiga.